No indication of increased infection rates using low‐dose alemtuzumab instead of anti‐thymocyte globulin as graft‐versus‐host disease prophylaxis before allogeneic stem cell transplantation. Issue 1 (27th December 2017) - Neumann, Thomas; Schneidewind, Laila; Thiele, Thomas; Pink, Daniel; Schulze, Meike; Schmidt, Christian; Krüger, William
Abstract: Background: Alemtuzumab as part of the conditioning protocol is effective in reducing graft‐versus‐host disease (GvHD), but may be associated with increased infection rates, especially when using high doses (ie, 100 mg). Methods: We performed a retrospective, single‐center, case‐control study analyzing the rates of neutropenic fever, cytomegalovirus (CMV) reactivation, Epstein‐Barr virus (EBV) reactivation, clinical manifest toxoplasmosis, and clinical manifest human herpesvirus‐6 (HHV6) infection using low‐dose alemtuzumab in comparison with anti‐thymocyte globulin (ATG) as GvHD prophylaxis before allogeneic stem cell transplantation. Forty‐four patients transplanted from unrelated donors between 2001 and 2012 were matched by age, diagnosis, and conditioning regimen and treated either with alemtuzumab 10 mg at day −2 (respectively, 20 mg in case of mismatch transplantation) or ATG. ATG Fresenius (10 mg/kg for 3 days) or Thymoglobulin (2 mg/kg for 3 days) were used. Results: Rates of CMV reactivation, EBV reactivation, and clinical manifest HHV6 infection or toxoplasmosis did not differ significantly between both groups until 2 years after transplantation. No case of post‐transplant lymphoproliferative disorder was observed. Also, rates of neutropenic fever during inpatient treatment after transplantation did not differ significantly in both groups. Conclusion: We saw no indication of increased infections rates when using low‐dose alemtuzumab as GvHD prophylaxis before allogeneic stem cell transplantation in this retrospective analysis.